Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s10840-005-4513-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Pulmonary Vein Stenosis in Patients Submitted to Atrial Fibrillation Ablation: A Comparison of the Selective Segmental Ostial Ablation vs the Circumferential Pulmonary Veins Ablation

Abstract: PV stenosis is a potential complication of SSOA not seen in CPVA. The study confirms than MRA is useful for identifying patients with asymptomatic PV stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 19 publications
1
12
0
2
Order By: Relevance
“…Its nature seems to be transient as documented in 69% of cases. This finding is consistent with Doppler data showing some degree of narrowing after the procedure that did not predict development of significant stenoses in long-term follow-up [21,22]. However, these results are contradictory to MRA data by Berkowitsch et al [25], who showed that minimal PV diameter reduction 1 day after ablation predicted development of significant stenosis in the long-term.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Its nature seems to be transient as documented in 69% of cases. This finding is consistent with Doppler data showing some degree of narrowing after the procedure that did not predict development of significant stenoses in long-term follow-up [21,22]. However, these results are contradictory to MRA data by Berkowitsch et al [25], who showed that minimal PV diameter reduction 1 day after ablation predicted development of significant stenosis in the long-term.…”
Section: Discussionsupporting
confidence: 85%
“…There is mounting evidence that the incidence of severe PV stenosis is declining with ablation strategies focused primarily on circumferential ablation around the ostia [12,21]. Some authors suggest that power titration using intracardiac echocardiography may further decrease the risk of this complication [12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 1 CPVA-1 and 2 CPVA-2 patients had postprocedural pericarditis that required nonsteroidal antiinflammatory treatment. Magnetic resonance angiogram performed before and 4 months after ablation in all patients of this series did not reveal any severe (Ͼ70%) PV stenosis 15 ; one patient of the CPVA-2 group showed a left superior PV narrowing of 55%.…”
Section: Tamborero Et Al Isolation Of the La Posterior Wall In Af Ablmentioning
confidence: 60%
“…3 It also has the advantage of limiting PV stenosis. 23 While isolation of the PV antra has become the cornerstone of all contemporary AF ablation procedures, patients with more advanced forms of AF, e.g. persistent rather than paroxysmal AF, are known to be less dependent on the PV antra for arrhythmia initiation and perpetuation.…”
Section: Pathophysiology Of Atrial Fibrillation and Atrial Fibrillatimentioning
confidence: 99%